LEADERSHIP STRATEGIES OF FEMALE PRINCIPALS IN IMPROVING THE QUALITY OF EDUCATION AT COKROAMINOTO SUKARESMI HIGH SCHOOL - Dede Setiawan; Mulyawan Safwandy Nugraha (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
This article is based on the fact that almost all over the world there are still unequal relationships and attitudes towards women and men. The director of SMA Cokroaminoto Sukaresmi (Cianjur Regency) pointed out that women can also be school principals or head wardens. The aims of this study are: 1. To describe the principal's management strategy in applying management style to improve the quality of education at Cokroaminoto Sukaresme High School. 2. At Cokroaminoto Sukaresme High School there was talk about a female principal management strategy that would enable teachers to improve the quality of teaching. Sukaresmi District, Cianjur Administrative District. 3. Cokroaminoto Sukaresmi High School, describes the factors that encourage and hinder the effectiveness of the leadership role of women as school principals in improving the quality of learning. Sukaresmi District, Cianjur Administrative District. This research method was applied with a descriptive qualitative approach, and the researcher used a purposive sampling method to determine the research topic. Methods of data collection in the form of observation, interviews and documentation using data sources from school principals, vice principals, teachers and students. Data analysis for this study consisted of data reduction, presentation and validation. Sources and techniques of triangulation The validity of the data using triangulation. The survey results are as follows. 1. The management style adopted by the director is transformational management. 2. Teacher approval by the school principal to improve teaching quality, namely a) participation in training b. Teacher awards are given by the school owner. 3. The factors that support school management to improve the quality of teaching are formal and informal organizations, mutual cooperation and kinship and the quality of teaching declared by the government. Facilities and infrastructure impede the quality of education for school principals, but graduates are less competitive.